Three genomes differentially contribute to the seedling lateral root number in allohexaploid wheat: evidence from phenotype evolution and gene expression. (19th July 2018) - Wang, Huifang; Hu, Zhaorong; Huang, Ke; Han, Yao; Zhao, Aiju; Han, Haiming; Song, Long; Fan, Chaofeng; Li, Run; Xin, Mingming; Peng, Huiru; Yao, Yingyin; et al.
Summary: Common wheat is an allohexaploid (BBAADD) that originated from the hybridization and polyploidization of the diploid Aegilops tauschii (DD) with the allotetraploid Triticum turgidum (BBAA). Phenotypic changes often arise with the formation and evolution of allopolyploid wheat, but little is known about the evolution of root traits in different wheat species with varying ploidy levels. Here, we reported that the lateral root number on the primary root (LRNPR) of synthetic and natural allohexaploid wheats (BBAADD) is significantly higher than that of their allotetraploid (BBAA) and diploid (AA and SS) progenitors, but is much lower than that of their diploid (DD) progenitors. The expression of the wheat gene TaLBD16, an ortholog of the Arabidopsis LATERAL ORGAN BOUNDARIES‐DOMAIN16/ASYMMETRIC LEAVES2‐LIKE18 ( LBD16 ), which is involved in lateral root development in Arabidopsis, was positively correlated with the LRNPR in diploid and allopolyploid wheats. In natural and synthetic allohexaploid wheats, the transcript of the TaLBD16 from the D genome ( TaLBD16‐D ) was relatively more abundant compared with TaLBD16‐A and TaLBD16‐B . Consistent with the observed variation in LRNPR, the divergence in the expression of TaLBD16 homoeologous genes occurred before the formation of polyploidy wheat. Collectively, our observations indicate that the D genome played a crucial role in the increased lateral root number of allohexaploid wheats compared with their allotetraploid progenitors, and that TaLBD16‐D was one of the key genes involved in the formation of lateral root number during wheat evolution. Significance Statement: The key finding of this study is that D genome plays a crucial role in the increased lateral root number of allohexaploid wheats as compared to their allotetraploid progenitors, and TaLBD16‐D was one of key genes involved in the formation of lateral root number during wheat evolution, which further expanded our knowledge about phenotypic variation and the underlying mechanism of wheat evolution.